Quantitative Modeling of the Impact of Video Content in the ITU-T G.1070 Video Quality Estimation Function - Joskowicz, Jose; López Ardao, J. Carlos; Sotelo, Rafael (Informática na educação teoria & prática, 2012)
In this paper we present an enhancement to the video quality estimation model described in ITU-T Recommendation G.1070 “Opinion model for video-telephony applications”, in order to include the impact of video content, for different display sizes and codecs. This enhancement provides a much better approximation of the model results with respect to the perceptual MOS values for a wide range of video contents. SAD (Sum of Absolute Differences) is used as an estimation of the video spatial-temporal activity, and is included as a new parameter in the model. The results are based on more than 1500 processed video clips, coded in MPEG-2 and H.264/AVC, in bit rate ranges from 50 kb/s to 12 Mb/s, in SD, VGA, CIF and QCIF display formats.